Conjugated polymers as promising electrode materials for lithium-ion batteries - Shi, Handa (Nanyang Technological University, 2025)
After the competition of almost half a century, lithium-ion battery (LIB) has become the most important energy storage device in modern society and industry. However, with the still fast-growing demand of batteries with different requirements, such as energy storage device in electric vehicles, traditional inorganic LIBs have exposed their drawbacks, many of the components are toxic and hard to degrade/recycle, lack of the raw resources and high cost in manufacturing process. LIBs with organic materials as electrodes has attracted more interest from researchers under this background. Organic materials as electrode materials have great flexibility in design, because of their rich chemistry in carbon backbones as well as eco-friendly for environmental protection and potentially cost-effective as many organic compounds can be obtained from recycled products and biomass